Bodies, selves, and human identity: A Conversation Between Transhumanism and the Apostle Paul - Kraftchick, Steven J. (Theology today, 2015)
In this article I propose the initiation of a conversation between biblical interpreters and proponents of transhumanism. Transhumanists recognize that the rapid expansion of technological innovation is changing our understandings of human behavior, thinking, and physical makeup. The vitality of the post/transhumanism debate about human identity suggests that a “biblical conversation” should be part of a larger conversation not only with theologians, but also the social entities who will hold forth on the values of human/machine transformations. It becomes ever more clear that this debate about human identity will be a real issue in the near future since we will undoubtedly improve our technological capacities and geometrically increase our prosthetic capacities, leading to a possible conclusion that the body itself is best understood as a “prosthesis.” For better or worse, Scripture is and will be adduced on both sides of the debate and often in the form of proof-texting rather than actual consideration of the materials. So, it seems not only reasonable but necessary to reopen the idea of how scriptural materials conceive of the body–self relationship. This is happening in some quarters (e.g. Thweatt-Bates, Cyborg Selves), but the use of biblical materials is not particularly strong. Hence, the viability of this project. This is a first foray into that matter and Paul is a good starting place since the question of the human being as an embodied being occupies a place of importance in many of his letters, especially Romans, 1 and 2 Corinthians, and 1 Thessalonians.